Enhanced mechanical, thermotolerance, and anti-yellowing performance of glass fibre filled polyether-ether-ketone composites with enclosed polyether-ether-ketone polyamide acid sizing agent - Hengjian Huan; Ruiyang Li; Mingxin Fan; Haiquan Guo; Lipeng Zhang; Jianying Zhao (Materials & Design, 2025)
The application potential of glass fiber reinforced polyether-ether-ketone (GF/PEEK) composites is hampered by weak interfacial adhesion. This problem originates from the low wettability and the thermal decomposition of the interlayer at high temperatures. To address this issue, an enclosed polyether-ether-ketone-polyamide acid (PEKA) was synthesized with the intention of improving the interfacial adhesion of GF/PEEK composites. Due to the high − temperature resistance of polyimide, the temperature of GF/PEEK at Td5% is 350 °C. The tensile strength increases by 70 % and the tensile modulus increases by 104 %. Additionally, the absorbance of GF/PEEK in the visible region has decreased by 73% at 600 nm. These results clearly illustrate the potential of PEKA as an excellent sizing agent. Which enhance the performance of GF/PEEK composites in terms of thermo-tolerance, mechanical strength, and anti − yellowing performance.